"I kind of gave up on it after a while, became too hard, closed my eyes, didn't want to know about it"—adults with type 1 diabetes mellitus describe defeat in the context of low social support. (22nd November 2018) - Hill, Kathleen; Ward, Paul; Gleadle, Jonathan
Abstract: Background: Type 1 diabetes mellitus (T1DM) is a lifelong condition that requires diligent self‐management to avoid complications. Living with T1DM is a considerable challenge and the inability to follow a prescribed regimen is often termed non‐compliance. However, this fails to acknowledge that for some people the barriers to glycaemic control may be insurmountable. Objective: This qualitative study explores the structural determinants, social context and lived experience of T1DM with 17 adults to understand influences on patterns of self‐care, engagement with and trust in health‐care services, and health outcomes. Results: Their stories tell us that strong social support is vital to disease adaptation and ongoing management. When social support is absent, the story is one of struggling with intensive diabetes management alone and difficulty controlling blood glucose levels. When confronted with suboptimal glycaemic control, participants isolated from social support developed combative relationships with health‐care providers and disengaged from health care. Their subsequent slide to chronic comorbid illness is steep and this study reveals the heartache and loss experienced when difficult life circumstances and low levels of social support have led to irreparable kidney damage. Conclusion: Patterns of poor glycaemic control viewed in the health‐care encounter without an understanding of the context or life circumstances in which they are occurring can lead to an inability to engage with health‐care services. Disengagement from services and the absence of specialist care further isolates people, leaving them managing their diabetes alone with limited success.